FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU KESEHATAN REPRODUKSI REMAJA PUTRI DI PROGRAM STUDI D-III KEBIDANAN STIKes HANG TUAH PEKANBARU - Kiki Megasari (Jurnal Ilmu Kebidanan, 2019)
Indonesia's population has reached around 262 million. The high population must be balanced with efforts to improve the quality of the population. One effort to improve the quality of human life can be done through efforts to improve reproductive health, especially for young people and the younger generation, this will increase the index of human resources in the future. This is because the number of adolescents in Indonesia today is quite large, one third of the composition of Indonesia's population is adolescents, so adolescent reproductive health remains one of the priority health programs in Indonesia because there are still many teenagers who pay less attention to reproductive health in Indonesia. at risk of reproductive health. This study aims to determine the relationship between knowledge and attitudes toward reproductive health behavior in the Midwifery Study Program STIKes Hang Tuah Pekanbaru. This type of research is Analytical Quantitative with Cross Sectional design method. The population in this study were all students of the Midwifery D-III Study Program at STIKes Hang Tuah Pekanbaru who attended 170 research participants with the Total Sampling technique and using Univariate and Bivariate Data Analysis. The results showed that there was a significant relationship between knowledge and behavior of reproductive health (pValue = 0.00 <0.05 POR = 4.850), and there was a significant relationship between attitudes and behaviors of reproductive health (pValue = 0.0042 <0.05 values POR = 7,700). It is expected that teachers or lecturers can cooperate with parents to provide good knowledge and guidance on reproductive health from an early age and can provide a good source of information about reproductive health. For teens to better equip themselves with knowledge about reproductive health, fill time with things that are useful and increase self-awareness to behave according to social and religious norms. Further research needs to be done on reproductive health with more developed variables and with broader respondents so that solutions can be found to solve reproductive health behavior problems.